1971
DOI: 10.1180/minmag.1971.038.294.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ‘deweylite’

Abstract: StJMMARY. Materials similar to the natural hydrated magnesium silicate mineral deweylite have been synthesized hydrothermally under low-temperature-low-pressure conditions from magnesia-silica gels. Optical, X-ray, infra-red, and DTA examinations have shown that both the natural and synthetic materials are mixtures of badly crystallized talc and badly crystallized serpentine. The mineral is thought to be a coarse mixture of these two components while the synthetic products are intimately interlayered. These ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Numerous studies were carried out and most of them confirmed the findings by Bakharev (2005). Vandeperre et al (2008a) reported that PC and magnesia hydrated independently in the first month, whereas in the study of Speakman and Majumdar (1971), 'deweylite', which is defined as a poorly crystalline magnesium silicate hydrate, is said to form naturally in hydrating Portland cements high in magnesia. When supplemental cementitious materials are used, interactions between magnesia and the other additives are revealed and various hydration products are confirmed.…”
supporting
confidence: 62%
“…Numerous studies were carried out and most of them confirmed the findings by Bakharev (2005). Vandeperre et al (2008a) reported that PC and magnesia hydrated independently in the first month, whereas in the study of Speakman and Majumdar (1971), 'deweylite', which is defined as a poorly crystalline magnesium silicate hydrate, is said to form naturally in hydrating Portland cements high in magnesia. When supplemental cementitious materials are used, interactions between magnesia and the other additives are revealed and various hydration products are confirmed.…”
supporting
confidence: 62%
“…This material is composed of a very fine-grained mixture of hydrous and possibly poorly ordered Mg-silicate phases with serpentine-, talc-, and stevensite-like compositions. Beinlich et al (2010) referred to this olivine breakdown product as a deweylite assemblage, following previous descriptions in the literature (Faust and Fahey, 1962;Speakman and Majumdar, 1971;Bish and Brindley, 1978). The formation of deweylite is generally attributed to low-temperature alteration or weathering of serpentinites at or close to the Earth's surface (e.g., Lapham, 1961;Wenner and Taylor, 1971).…”
Section: Description Of the Starting Materialsmentioning
confidence: 97%
“…This alteration product bears chemical resemblance to sepiolite but it may also be an extremely fine-grained intergrowth of several mineral phases. Such an intergrowth has been described in the literature as deweylite and is vaguely defined as a compositionally variable mixture of poorly crystalline serpentine and talc or serpentine and stevensite (Faust and Fahey, 1962;Speakman and Majumdar, 1971;Bish and Brindley, 1978). Generally, the deweylite assemblage is interpreted to form at low temperatures, i.e., <180°C (Speakman and Majumdar, 1971) or even $50°C (Faust and Fahey, 1962).…”
Section: Type-1 Clasts (Incipient Alteration): Texture and Mineral Comentioning
confidence: 97%